Pengaruh Beban Kerja, Stres Kerja Dan Semangat Kerja Terhadap Kinerja Karyawan Koperasi Unit Desa (KUD) Karya Bhakti Ngancar Kabupaten Kediri - Kumalasari, Yana; Dewi, Anita Sumelvia; M, Agung Pambudi (Universitas Maritim AMNI Semarang, 2023)
This research aims to explain and prove the hypothesis regarding whether there is an influence on workload, work stress and work morale employee performance of KUD Karya Bhakti Ngancar Kediri. This type of research using descriptive research with quantitative methods with techniques Sampling is non-probability sampling with a purposive method sampling where the population was 57 employees and the sample was 34 permanent employees. The analysis techniques used are validity tests, reliability tests, classical assumption test, multiple linear regression test, t test (partial), F test (simultaneous) as well coefficient of determination (R2) processed using the SPSS version 25 program. The research results show that Work Load (X1), Work Stress (X2) and Work Morale (X3) have a significant effect simultaneously and partially on Employee Performance (Y). In this panel it is also known that coefficient of determination (R2) Adjusted R square Work Load, Work Stress and Work Morale has an influence of 97.2% in influencing Employee performance, while the remaining 2.8% is influenced by variables others that were not discussed in this study so that they are for further research using variables outside this research. The study implies that The performance factors of an organization are influenced and can be improved through load work, work stress, and work morale.